Mixed Boundary Value Problems for a Class of Fractional Differential Equations with Impulses (Journal of Nonlinear Modeling and Analysis, 2024)
We investigate a class of mixed boundary value problem of nonlinear impulsive fractional differential equations with a parameter. The uniqueness of this problem is proved by applying Banach fixed point theorem.
Keywords: Fractional differential equations; Boundary value problem; Impulsive; Uniqueness.